The importance of the law of the wall - Mandal, B.C.; Mazumdar, Himadri Pai (Zielona Góra: Uniwersytet Zielonogórski)
This paper reports some results of turbulent boundary layer computation. The calculation is made assuming that law of the wall is valid throughout the boundary layer. Simple relations are proposed for friction for a smooth pipe and a flat plate at zero incidence. The results are compared with recent measurements. Encouraging results are obtained for both the cases of flows.
Keywords: boundary layer; flat plate; friction factor; skin friction